1981
DOI: 10.1128/jcm.13.2.301-308.1981
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of parameters affecting the hemagglutination activity of Escherichia coli possessing colonization factor antigens: improved medium for observing erythrocyte agglutination

Abstract: The hemagglutination (HA) activity of two strains of Escherichia coli, each possessing different colonization factor antigens (CFA), was examined under different test conditions. The effects of ionic strength, temperature, pH, cations, and reaction surface on erythrocyte (RBC) agglutination were analyzed. Strain H-10407 (CFA/I) caused the agglutination of human, bovine, and chicken RBC, whereas strain CL-9699 (CFA/II) agglutinated only bovine and chicken RBC. The HA activity of both strains increased with decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The different purified P fimbriae did not readily agglutinate human erythrocytes. To improve hemagglutination, the low-ionic-strength buffer of Sedlock et al (30) was applied, but without success. However, after treatment of the erythrocytes with neuraminidase, the Pl and p2k erythrocytes became agglutinable by all four P fimbriae preparations.…”
Section: Resultsmentioning
confidence: 99%
“…The different purified P fimbriae did not readily agglutinate human erythrocytes. To improve hemagglutination, the low-ionic-strength buffer of Sedlock et al (30) was applied, but without success. However, after treatment of the erythrocytes with neuraminidase, the Pl and p2k erythrocytes became agglutinable by all four P fimbriae preparations.…”
Section: Resultsmentioning
confidence: 99%
“…Since most bacterial attachment and hemagglutination reflect the microorganism's ability to overcome repulsive (negative) electrostatic surface changes (12), it is not surprising that Sedlock et al (29) have found that bacterial hemagglutination assays can be made more sensitive by lowering the pH and ionic strength of the buffering medium used. Failure to recognize and control the above-mentioned variables may account for some of the reported discrepancies in B. bronchiseptica's hemagglutinating ability.…”
Section: Sismentioning
confidence: 99%
“…Both human (Community Blood and Plasma, Folcroft, Pa.) and bovine erythrocytes (GIBCO Diagnostics, Madison, Wis.) were used in this study. The erythrocyte suspensions were prepared in a low-ionic-strength, isotonic buffer, the properties of which have been described elsewhere (14). The buffer consisted of 200 mM D-sorbitol, 50 mM D-mannose and 25 mM 2-(Nmorpholino)ethanesulfonic acid (Calbiochem, La Jolla, Calif.).…”
Section: Methodsmentioning
confidence: 99%